Mechanical Properties of Concrete with Recycled Bottle Glass Powder Substitute - Tatanka, I Made; Bali, Ika; Sudjatmiko, Eddy (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2024)
Concrete is a material that is widely used in the construction of structural buildings. One of the influential factors for obtaining high quality concrete is the aggregate gradation. If the aggregate gradation has a small size and varies, it can reduce the porosity of the concrete so that the concrete becomes denser which makes the quality of the concrete high. In order to use aggregates with fine gradations, this study proposes glass powder derived from glass bottle waste as a partial replacement for fine aggregates. The glass powder used is in the sizes about 0.150 mm - 0.075 mm. Then, the maximum size of 15 mm for the coarse aggregate and the fine aggregate with the gradation of zone 4 (fine sand) were used for the concrete mix. The purpose of this study is to investigate the mechanical properties of concrete i.e. the compressive and split tensile strength of concrete with glass powder as a partial substitution of fine aggregates with a percentage of 10%, 15%, and 20% at a concrete age of 28 days. This study uses the testing method that refers to ASTM standard. From the test results, it was found that the compressive strength of concrete with 20% glass powder variation (GPC 20%) increased by 11.32% with a value of 38.97MPa compared to the compressive strength of normal concrete (NC) with a value of 35.01 MPa. For the split tensile strength, the concrete with a 20% glass powder variation increased by 15% with a value of 2.71 MPa compared to the split tensile strength of normal concrete with a value of 2.36 MPa. The results showed that the use of glass powder as a partial replacement for fine aggregate in this study was reasonably good to improve its mechanical properties.